(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In the modern economy, regional competitiveness increasingly depends on how effectively investment resources are transformed into innovation, productivity, and sustainable growth. For this reason, modeling the processes of effective use of investment potential has become an important tool for understanding how regions can accelerate innovative development and improve their socio-economic performance. The central idea is simple: investment alone does not guarantee growth; what matters is the quality of its allocation, coordination, and conversion into tangible economic results.